Effects of combined nutrient supply treatments on some physiological parameters of autumn wheat - Kaprinyák, Tünde; Láposi, Réka; Bekő, László; Tóth, Szilárd (Acta Agraria Debreceniensis, 2018)
The Fleischmann Rudolf Research Institute in Kompolt is not only famous for plant breeding but the institute also surveys the effects of different nutrient supply methods since 1918. In 2017, we joined this research supported by EFOP 3.6.1 project. Our aim was to investigate photochemical processes – which is one of the most determinant in case of yield – of crops by in vivo field measurements. We measured the chlorophyll content of leaves using Minolta SPAD 502. We used miniPAM fluorometer to determine actual photochemical efficiency and non-photochemical quenching of PSII during natural light conditions and also to evaluate the pigment (chlorophylls and carotenoids) and water content of leaves we applied field spectrophotometer (ASD FieldSpecPro 3). We utilized these methods by various treatments (1. treatment with soil bacteria + head and base fertilizer; 2. treated by only head fertilizer; 3. treated by only base-fertilizer) in field experiment of autumn wheat (4.1–2.43–1.19 ha) in June, 2017. The difference between treatments was clearly detectable. In the case of the first treatment, physiological processes were more intense and the ripening occurred earlier. The obtained yield was the highest in the case of the area treated by soil bacterial. Based on the results, the first treatment can be recommended in practice.